Menisoxoisoaporphine A, a novel oxoisoaporphine alkaloid from Menispermi Rhizoma, inhibits inflammation by targeting PDE4B - Qiao, Xin; Cao, Xiaojuan; Xu, Shuang; Wang, Cunlin; Guo, Rui; Yao, Xiaojuan; Zhang, Qiong (Frontiers in Pharmacology, 2024)
Background Dysregulated and excessive inflammatory reactions can lead to tissue damage, which is the underlying cause of most human diseases. Menisoxoisoaporphine A (MA), a novel oxoisoaporphine alkaloid, was obtained from Menispermi Rhizoma, a traditional Chinese medicinal herb used in the treatment of inflammatory conditions in clinical practice. This suggests that MA has very promising potential for the development of anti-inflammatory therapeutics. Hence, this study aims to investigate the anti-inflammatory effects and underlying mechanisms of MA. Method The anti-inflammatory effects of MA were evaluated in lipopolysaccharide (LPS)-induced mouse macrophage RAW264.7 cells. Its underlying mechanisms were explored through RNA sequencing and Western blotting. The binding modes and interactions sites between MA and phosphodiesterase 4B (PDE4B) were predicted using molecular docking and validated by molecular dynamics simulation. Results MA treatment significantly reduced LPS-induced morphological changes, inflammatory cytokine relesae, and proinflammatory genes expression in RAW264.7 cells compared to the LPS-induced controls. Transcriptome sequencing analysis suggested that PDE4B might be a key target for MA to exert its therapeutic effect. Mechanismly, MA directly acted on Tyr405 site of PDE4B, thus leading to a sustained elevation of the cyclic adenosine monophosphate (cAMP) levels, which subsequently inactivated NF-κB signaling pathway by phosphorylating protein kinase A (PKA). MA inhibited the NF-κB-mediated inflammatory response depending on PDE4B. Conclusion MA, a natural and novel compound, exerted anti-inflammatory effects in LPS-induced RAW264.7 macrophage cells. It demonstrated a strong binding ability to the Tyr405 sites of PDE4B, thereby inhibiting NF-κB signaling pathway by regulating the cAMP-PKA axis. Elucidating the interaction between MA and PDE4B holds significant potential for the advancement of innovative therapeutic strategies aimed at inflammatory diseases. By strategically modulating this interaction, it may be feasible to achieve more precise regulation of inflammatory responses, thereby offering promising therapeutic benefits for conditions such as rheumatoid arthritis, asthma, and inflammatory bowel disease.